Multimodal Pattern Recognition of Social Signals in Human-Computer-Interaction First IAPR TC3 Workshop, MPRSS 2012, Tsukuba, Japan, November 11, 2012, Revised Selected Papers - Schwenker, Friedhelm; Scherer, Stefan; Morency, Louis-Philippe (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the thoroughly refereed post-workshop proceedings of the First IAPR TC3 Workshop on Pattern Recognition of Social Signals in Human-Computer-Interaction (MPRSS2012), held in Tsukuba, Japan in November 2012, in collaboration with the NLGD Festival of Games. The 21 revised papers presented during the workshop cover topics on facial expression recognition, audiovisual emotion recognition, multimodal Information fusion architectures, learning from unlabeled and partially labeled data, learning of time series, companion technologies and robotics.